2016
DOI: 10.1093/heapro/daw017
|View full text |Cite
|
Sign up to set email alerts
|

Association of social capital at the individual level with physical activity in communities with high mortality in Korea

Abstract: The aim of this study was to investigate the association of various dimensions of social capital at the individual level with physical activity. We used data from community health interviews conducted in 40 sub-municipal-level administrative units with high mortality from August to October in 2010, 2011 or 2012 for health projects in South Korea. The 8800 study subjects included 220 adults from each administrative unit, who were sampled systematically using the resident registration database. The physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Furthermore, income level, which is an important factor for determining the level of health [ 23 ], also affected the coronavirus hospital readmission rate. A lower level of income led to a higher mortality rate from COVID-19, according to the COVID-19 mortality study in Sweden [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, income level, which is an important factor for determining the level of health [ 23 ], also affected the coronavirus hospital readmission rate. A lower level of income led to a higher mortality rate from COVID-19, according to the COVID-19 mortality study in Sweden [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We reverse-coded items so that higher scores indicate more control. These items have been used in previous research studies and found to be reliable (Cronbach's alpha ¼ 0.83) (Taylor et al, 2012(Taylor et al, , 2017Kim et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-one articles were categorized in this group. The identified indices were 1) community involvement, 68,69 different forms of social participation, 35,39,45,56,61,70-77 social club membership, 40 organizational membership, 78 civic engagement, 33 partnership with the community, 72 and health democracy. 79,80 As another index, gay community involvement was defined as “a new multidimensional measure of the type and intensity of participation in a variety of activities within the gay community.” 68 Two studies introduced “participation” as one of the social capital components, 61,75 and two other studies defined the index in a clear way: “How actively the person has taken part in the activities of formal and informal groups as well as other activities in society during the past 12 months,” 73 and “Sum of the participation proportions of organizations in each community.” 56 In seven studies, the index was measured as an indicator of social capital.…”
Section: Resultsmentioning
confidence: 99%
“…79,80 As another index, gay community involvement was defined as “a new multidimensional measure of the type and intensity of participation in a variety of activities within the gay community.” 68 Two studies introduced “participation” as one of the social capital components, 61,75 and two other studies defined the index in a clear way: “How actively the person has taken part in the activities of formal and informal groups as well as other activities in society during the past 12 months,” 73 and “Sum of the participation proportions of organizations in each community.” 56 In seven studies, the index was measured as an indicator of social capital. 35,43,56,71,73,75,78…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation